The Predicted Trainer and Training Environment Influence toward Vocational Training Effectiveness in Bahrain - Yaqoot, Ehsan Saeed Idrees; Wan Mohd Noor, Wan Shakizah; Mohd Isa, Mohd Faizal (Journal of Technical Education and Training, 2021)
This research aims to examine the development of vocational training issues faced in the public sector extent in Bahrain. Training implication should not be overlooked in delivering the required capabilities and knowledge in performing a certain task. The proposed research framework is established with a reference to the training evaluation model of Kirkpatrick, however, the study analyzes one of four levels for evaluating training effectiveness, those are reaction, learning, behavior, and the level of interests; result. A quantitative research design is applied. The survey instrument comprised of 29 items that tested two hypotheses. It was distributed to 382 respondents according to their interests using the purposive sampling technique adopted across 4 different public sector organizations in Bahrain. However, 128 were the usable ones from the returned 155 questionnaires. It is discovered that the contextual factor namely trainer has a positive influence on the training programmes implemented in this sector. Also, surprisingly this study unlocks an interesting and challenging area in the training environment for scholars in exploring and improving the quality of training programmes. The study essentially contributes to the paucity in training antecedents and training effectiveness in the public sector literature-related research. Hence, enhancing training effectiveness requires the management and practitioners to enhance the training antecedents to ensure the achievement of training/organization objectives. Understanding the importance of these certain types of factors will help the management to enhance the trainees’ gaining and therefore their performance. Thus, training antecedents should play an important role before trainee’s training. Managers should as well be involved with sponsoring reliable factors and drawing up a comprehensive vision.